2001
DOI: 10.1007/pl00001184
|View full text |Cite
|
Sign up to set email alerts
|

Microtremor Measurements for the Microzonation of Dinar

Abstract: Ð The geotechnical site conditions in Dinar town located in western Turkey were investigated after the 1995 Dinar earthquake based on borings, in situ penetration tests, seismic wave velocity measurements, and microtremor records. The variation of damage distribution within the town was evaluated with respect to 23 district damage ratios calculated, based on the detailed damage survey conducted by the General Directorate of Disaster Aairs. Site ampli®cations were estimated from microtremor spectral ratios and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 6 publications
0
24
0
1
Order By: Relevance
“…Extensive investigations were performed before and after the earthquake to determine the geological and geotechnical properties of the Dinar basin. These include numerous 30 m deep boreholes opened in different parts of the town (ERKEN et al, 1999;ANSAL et al, 2001;BAKIR et al, 2002). Comprehensive seismic refraction surveys were also performed within the town to provide shear-wave velocity profiles of subsurface soil to 20 m depth (TURKER et al, 1996).…”
Section: Tectonics and Geologymentioning
confidence: 99%
See 4 more Smart Citations
“…Extensive investigations were performed before and after the earthquake to determine the geological and geotechnical properties of the Dinar basin. These include numerous 30 m deep boreholes opened in different parts of the town (ERKEN et al, 1999;ANSAL et al, 2001;BAKIR et al, 2002). Comprehensive seismic refraction surveys were also performed within the town to provide shear-wave velocity profiles of subsurface soil to 20 m depth (TURKER et al, 1996).…”
Section: Tectonics and Geologymentioning
confidence: 99%
“…SUCUOGLU et al (2003) showed that at most periods, the response spectrum from the Dinar accelerogram is smaller than the design response spectrum specified for zone 1 in the Turkish seismic design code. 90 people died and about 40% of the total buildings collapsed or were heavily damaged during the Dinar earthquake (ANSAL et al, 2001). The majority of housing and other settlements are located in the Dinar basin, and some settlements are located in the mountainous area.…”
Section: Datamentioning
confidence: 99%
See 3 more Smart Citations